2005
DOI: 10.1111/j.1365-2028.2005.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal resource partitioning and climatological influences on colony flight and foraging of stingless bees (Apidae; Meliponini) in Ugandan tropical forests

Abstract: We studied the flight activity of two stingless bee species (Meliponula ferruginea and Meliponula nebulata) and the environmental factors influencing their flight. Two morphs of M. ferruginea were studied: M. ferruginea (brown) in Budongo forest and M. ferruginea (black) in Bwindi Park. The two bee species exited their nests in characteristically distinct foraging bouts suggesting that the recruitment methods used may be direct leading or 'piloting'. The number of individuals in a returning bout was less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 19 publications
1
23
0
8
Order By: Relevance
“…The recruitment strategies of the bees to food sources may probably explain the differences in diversity. In a related study (Kajobe and Echazarreta, 2005) found that workers of M. ferruginea exited their nests in characteristically distinct foraging bouts suggesting that the recruitment methods employed may be direct leading or "piloting" (Esch et al, 1965;Esch, 1967;Johnson, 1987). Such recruitment trait could have led to the reduced diversity in nectar sources for M. ferruginea.…”
Section: Behavioural Factors Regulating Partitioning Of Nectar Resourcesmentioning
confidence: 99%
“…The recruitment strategies of the bees to food sources may probably explain the differences in diversity. In a related study (Kajobe and Echazarreta, 2005) found that workers of M. ferruginea exited their nests in characteristically distinct foraging bouts suggesting that the recruitment methods employed may be direct leading or "piloting" (Esch et al, 1965;Esch, 1967;Johnson, 1987). Such recruitment trait could have led to the reduced diversity in nectar sources for M. ferruginea.…”
Section: Behavioural Factors Regulating Partitioning Of Nectar Resourcesmentioning
confidence: 99%
“…Por exemplo, no hábitat em que a umidade relativa variou pouco, a atividade de voo de M. scutellaris continuou a apresentar relação significativa apenas com a temperatura. Do mesmo modo, a constatação de que é incomum o forrageio sob alta umidade relativa entre os pequenos Meliponini em hábitats úmidos tropicais (KLEINERT-GIVANNINI, 1982;HILÁRIO et al, 2000HILÁRIO et al, , 2001KAJOBE & ECHAZARRETA, 2005;TEIXEIRA & CAMPOS, 2005) não pode ser dissociada de respostas às variações simultâneas na temperatura ao longo do dia.…”
Section: Discussionunclassified
“…A temperatura, umidade relativa do ar, intensidade luminosa, pluviosidade e velocidade do vento são fatores que, isolados ou em conjunto, exercem grande influência sobre a atividade de voo dessas abelhas (KLEINERT-GIOVANNINI & IMPERATRIZ-FONSECA, 1986;HILÁRIO et al, 2000;KAJOBE & ECHAZARRETA, 2005).…”
unclassified
“…e Nannotrigona testaceicornis, durante condições relativamente adversas: chuva ou céu encoberto e temperaturas de 19 a 20 °C. Kajobe & Echazarreta (2005) também relataram o forrageamento de Meliponula nebulata sob condições de neblina e garoa. Em análise quantitativa, Buriolla (1988) relatou a redução de 22% em média na atividade de vôo de A. mellifera durante chuva.…”
Section: Discussionunclassified
“…Nos trabalhos sobre a influência de fatores abióticos na atividade de vôo de abelhas, comumente é mencionado que a precipitação pluviométrica causa a interrupção da atividade externa (Oliveira 1973, Iwama 1977, Kleinert-Giovannini 1982 ou a diminuição desta atividade (Michener 1974, Sommeijer et al 1983, KleinertGiovannini & Imperatriz-Fonseca 1986, Roubik 1989, Kajobe & Echazarreta 2005. Entretanto, até o momento a influência da precipitação pluviométrica sobre a atividade de vôo não foi quantificada.…”
Section: Introductionunclassified